Biorhythmic tests to rate gender-specific urgent adaptation in junior athletes under latitudinal relocation - Povzun, A. A.; Povzun, V. D.; Apokin, V. V.; Usaeva, N. R. (Theory and Practice of Physical Culture, 2018)
The study applied biorhythms rating tools to rate effects of time zone offsets on the gender-specific fast adaptation processes in junior sprinters, permanent residents of the Khanty-Mansi Autonomous Region. Tests under the study were designed to rate, among other things, the gender-specific responses of the athletes` cardiovascular systems. Subject to the study were junior (16-18 year-old) sprinters (n=33, including 15 males and 18 females). The study data and rhythm structure analyses failed to show any adaptive capability changes directly attributable to the time zone offsets; with the gender-specific variations in the urgent adaptive capability rates (that secure adequate regulatory system transformations and relevant sport benefits for young people) being associated with high-intensity physical loads. We believe that the changes in the main parameter and activity of the central ergotropic and humoral-metabolic HR regulation mechanisms are due to the high-intensity physical loads and stresses rather than to the time zone offsets and pre-flight conditions. It should be emphasized in this context that objective profiles of the autonomic status variations may be highly important for interpretation of the biorhythmic data related to the body adaptive capability and functionality resource; since even the stable rhythms associated with changes in the vegetative tonus may be interpreted in different ways and have different physiological implications.